Size Distribution and Anti-trust - Luca Lambertini; Dan Sasaki (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
Extensive literature notwithstanding, effects of the size distribution of firms on consumers' surplus and on social welfare leaves room for further exploration. In this paper we discover that size distribution imposes two counter-balancing effects on aggregate surplus of the industry : [i] even distribution of firm sizes typically facilitates tacit collusion compared to slightly uneven distribution, whilst [ii] very uneven distribution resembles monopoly. The trade-off between these two counterforces can make the overall welfare effect of firms' size distribution (given a fixed number of firms) non-monotone in the degree of concentration.
Keywords: 330